Rasuah Dan Integriti Dalam Pentadbiran Awam Di Malaysia: Sorotan Literatur - Izawati Wook; Arif Fahmi Md Yusof; Hasnah Hj. Haron (Universiti Teknologi MARA Press, 2024)
Voice of Academia Vol. 18, Issue (2) 2022